Expand:(I) (2a+b) ^3 plz help
Answers
Answered by
3
Answer:
if you got the answer correct please mark it brainliest and follow me
Attachments:
![](https://hi-static.z-dn.net/files/d7d/a217480ad48ddd74c74bcdbcd0d91195.jpg)
Answered by
2
Answer:
(2a + b)3 = (2a)3 + (b)3 + 3 × 2a × b(2a + b)
[(a + b)3 = a3 + b3 + 3ab (a + b)]
= 8a3 + b3 + 6ab (2a + b)
= 8a3 + b3 + 12a2b + 6ab2
Step-by-step explanation:
hope it helps you
Similar questions
Geography,
5 months ago
English,
5 months ago
Business Studies,
10 months ago
Science,
10 months ago
History,
1 year ago